A study on cloning and expression of HIV-1 NEF protein in HEK 293 cells by transient transfection - Balakrishnan, K.V.; Abdullah, B.M.; Alsayed, R.; Huri, H.Z.; Hairunisa, N.; Ibrahim, A.E.; Yousif, E. (Research Journal of Pharmaceutical, Biological and Chemical Sciences, 2016)
HIV continues to be a major global public health issue, there were approximately 34 million people living with HIV in 2011. However, the development of anti-viral has blunted the AIDS epidemic in the Western world but globally the epidemic has not been curtailed. Nef is one of these accessory genes that are only present within HIV and SIV genome and thought to play a key role in the progression to AIDS. The given its central role in HIV pathogenesis, Nef considered as a potential anti-viral target for preventing or at least delaying pathogenesis. The biologically active 27 kDa myristoylated Nef protein expressed from HEK 293 cells is a protein model to be used for significantly specific antibody production to lower the pathogenicity of HIV infection. To express the this protein model, pQBI-6His a mammalian expression vector constructed with base pair 5504 to express 627 bp HIV-1 Nef under CMV promoter. It shows that targeted 27 kDa HIV-1 Nef was not successfully expressed in HEK 293 cells either in transient transfection when transfected. However, nontargeted HIV-1 Nef was detected in western blot by anti-Nef (anti mouse) manufactured by Thermo scientific. The ability of not expressing the targeted myristoylated 27 kDa nef protein was to various unpreventable factors due to time limitation and lacking of skills in the filed cloning and cell culture.